Systematic review of instruments for the assessment of the death and dying process applying the COSMIN methodology - Meneguin, Silmara [UNESP]; Benichel, Cariston Rodrigo [UNESP] (Elsevier, 2024)
Death is a singular experience, the setting of which has changed throughout history. Numerous notions about death have undergone significant changes whether due to advances in Western religiousness, increased knowledge on the treatment of diseases or the fast pace of daily routines linked to hospitalization, which has become a viable end-of-life option. Despite the importance of the issue, to the best of our knowledge, no systematic reviews are found on instruments available in the literature for the assessment of the quality of the dying process or the measurement properties of such instruments. This study aimed to analyze the measurement properties of instruments available in the literature for the assessment of the death and dying process. Methods A systematic review was conducted in accordance with the PRISMA statement. Searches were conducted in the Web of Science, PubMed, CINAHL, Scopus and LILACS databases. The COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) were used for the assessment of the measurement properties of the instruments and quality of the evidence of the articles. Results Seventeen articles were included. The main instrument was Quality of Dying and Death translated into German, Persian, Chinese and Spanish, with an average of 24 items distributed among six dimensions. Measurement properties were assessed mainly by classical test theory using confirmatory factor analysis with the TLI, CFI and RMSEA. Most instruments had good responsiveness and adequate fit of models adopted (CFI and TLI > 0.9 and RMSEA ≤0.08), with a high quality of evidence for structural validity as well as internal consistency and reliability (Cronbach's alpha coefficient and intraclass correlation coefficient both higher than 0.7). The main aspects that reduced the quality of the evidence were partial results and the lack of information on cultural validity and criterion validity. Conclusion Instruments for the assessment of the quality of death exhibited sufficient evidence of high quality for bifactorial structural validity, internal consistency, reliability and responsiveness and moderate, partially sufficient evidence for criterion validity and cultural validity. Metrics founded on classical test theory prevailed and the main instrument was Quality of Dying and Death. References Gellie A, Mills A, Levinson M, Stephenson G, Flynn E. Death: a foe to be conquered? Questioning the paradigm. Age and Ageing. 2015;44(1):7–10.